Effect of inclusion on 4H-SiC during nano-scratching from an atomistic perspective. (12th August 2021) - Huang, Yuhua; Wang, Miaocao; Li, Jinming; Zhu, Fulong
Abstract: Inclusion, a common three-dimension defect, can be introduced during SiC epitaxy. In this study, we constructed nano-scratching molecular dynamics models embedded in two common types of inclusion—C-inclusion and Si-inclusion—to explore the effect of inclusion during scratching. Furthermore, the microstructure and atomistic behavior, surface morphology, scratching force, stress, and temperature were analyzed to bridge the simulation and processing parameters. The results showed that inclusion could affect the microstructure and atomistic behavior, and machinability. To eliminate inclusion completely, high penetration depth was required, but it would promote the process parameter sensitivity of inclusion. In summary, the behavior of C-inclusion embedded in SiC more likes a hard particle, while the behavior of Si-inclusion embedded in SiC more likes a soft particle.